David Serrano-Blanquer, Les dones et camps nazis, 2003 - Stöcker, Joanna (Czasopismo Prawno-Historyczne, 2004)
Recenzja: David Serrano-Blanquer, Les dones et camps nazis, Pórtic 2003, Barcelona, ss. 185.